THE RELATIONSHIP OF HEALTH EDUCATION TO ELDERLY KNOWLEDGE ABOUT HOW TO PREVENT HYPERTENSION IN THE ELDERLY IN AEK BOLON JAE VILLAGE, BALIGE DISTRICT - Jane Wilda Irmawati Sirait (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
Hypertension is still a health problem in the elderly group. Increased age is often followed by degenerative diseases and health problems in the elderly group. Therefore, researchers are interested in conducting a study entitled Relationship of health education to elderly knowledge on how to prevent hypertension in the elderly in Aek Bolon Jae Village, Balige District in 2022. This study was conducted in April-June 2017 with a population of 198 people while the sample used as many as 99 people using the formula from lemeshow book using simple random sampling techniques. The results of this study stated that health education has a relationship to the knowledge of the elderly in Aek Bolon Jae Village, Balige District in 2022, because p value < 0.05. It is expected that it can be increased the knowledge of elderly posyandu cadres about hypertension and how to prevent it and improve the ability of cadres in providing counseling so that counseling to the elderly is more effective. Education Institutions provide elderly posyandu material which is one of the basic health services through courses related to elderly services both integrally and specifically cases of hypertension in the elderly and prevention methods. The results of this study as preliminary data to conduct other research on the elderly with different variables.